2021
DOI: 10.1038/s41598-021-96131-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence characteristics of human papillomavirus (HPV) infection among women receiving physical examinations in the Shangcheng District, Hangzhou city, China

Abstract: This paper aimed to investigate the characteristics of female HPV infection in the Shangcheng District, Hangzhou city, China. The retrospective study was designed to analyze the HPV prevalence rate of 22,382 women receiving physical examinations from 2016 to 2020 in the Shangcheng District of Hangzhou city in China. A commercial kit was designed to detect the HPV genotypes. Trends were examined for age-specific groups (≤ 30 years, 31–44 years, 45–54 years, 55–64 years,  ≥ 65 years). A receiver operating charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Meanwhile, the regions of Western and Middle China have similar HPV rates of 13.5% (Shannxi) [ 29 ], 12.6–15.29% (Sichuan) [ 30 , 31 ], 12.09% (Henan) [ 32 ], 13.56% (Jiangxi) [ 33 ], and 13.88% (Hunan) [ 34 ]. In contrast, HPV prevalence in Eastern China is reported to vary greatly from 10.6% (Jiangsu) [ 17 ] to 22.41% (Zhejiang) [ 35 ]. In Zhejiang [ 36 ], data from routine physical examinations performed indicate the prevalence of HPV is 13.6%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the regions of Western and Middle China have similar HPV rates of 13.5% (Shannxi) [ 29 ], 12.6–15.29% (Sichuan) [ 30 , 31 ], 12.09% (Henan) [ 32 ], 13.56% (Jiangxi) [ 33 ], and 13.88% (Hunan) [ 34 ]. In contrast, HPV prevalence in Eastern China is reported to vary greatly from 10.6% (Jiangsu) [ 17 ] to 22.41% (Zhejiang) [ 35 ]. In Zhejiang [ 36 ], data from routine physical examinations performed indicate the prevalence of HPV is 13.6%.…”
Section: Discussionmentioning
confidence: 99%
“…For HPV detection and genotyping, two commercial HPV Genotyping Kits (Shanghai ZJ Bio-Tech Co., Ltd.) were used to detect fifteen high risk (HR)-HPV types (16,18,31,33,35,39,45,51,52,56,58,59, 66, 68, and 82) and a combination of two low-risk (LR)-HPV types (6/11) with use of TaqMan real-time fluorescent quantitative polymerase chain reaction (PCR) using a Slan-96P Real-time PCR System assay (Hongshi Medical Technology Co., Ltd., Shanghai, China). Samples were reported to be HPV positive if any of the 17 HPV DNA types were detected.…”
Section: Sample Collection Hpv Detection and Genotypingmentioning
confidence: 99%
“…We evaluated HR-HPV cases in three groups of type 16, type 18, and other types based on the data. Wang et al reported that prevalence rates of type 16 and 18 were 3.95%, and 3.27% in Chinese women, respectively (Wang et al 2021). In a study conducted with Mexican women, the most common types were type 16 (43%) and 18 (42%) (López Rivera et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, China has implemented rigorous epidemic prevention measures over the course of 3 years, surpassing those of most other countries worldwide. 39 The investigation of the correlation between HPV infection and long-term control measures to 22.41%, [40][41][42] with a higher prevalence observed among clinicbased patients than in general population, ranging from 17.92% to 50.64%. 43,44 In the current investigation, the aggregate HPV infection rate among outpatients admitted at PUMCH during the prepandemic period was found to be 33.54%.…”
Section: Discussionmentioning
confidence: 99%
“…High-risk HPV (HR-HPV) types, such as HPV16, 18,31,33,35,39,45,51,52,56,58,59, and 68, are known to cause cervical intraepithelial neoplasia, cervical cancer, and other malignant lesions. 6 Conversely, low-risk HPV (LR-HPV) types, including HPV6, 11,42,43,44,54,61,70,72, and 81, are associated with benign lesions such as genital warts. 7,8 HPV16 and 18 are causally linked to approximately 70% of cervical cancer cases, whereas HPV6 and 11 are responsible for 90% of condyloma acuminatum cases.…”
Section: Introductionmentioning
confidence: 99%